Farmers’ Appraisal on Okra [Abelmoschus esculentus (L.)] Production and Phenotypic Characterization: A Synergistic Approach for Improvement - Ibitoye, Dorcas Olubunmi; Kolawole, Adesike Oladoyin (Frontiers in Plant Science, 2022)
Okra (Abelmoschus esculentus (L.) Moench is a nutrient-rich economically important vegetable crop grown in tropical and sub-tropical parts of the world. Okra is one of the horticultural mandate crops of the National Horticultural Research (NIHORT), Ibadan, Nigeria. It is an under-studied crop in terms of genetic improvement. As a response to demand from farmers’ for improved varieties, efforts commenced towards developing novel okra varieties in the institute. However, successful and sustainable crop improvement programme depends on the identification of market-driven demands and the availability of variation in the crop germplasm. In view of the above, this study started with appraisal study to assess the current situation of okra production and to identify farmers’ preferred traits for establishing breeding priorities Result of the participatory rural appraisal revealed lack of improved varieties, diseases, pests and drought as some of the important constraints affecting okra productivity. The quest to assess variability in the collected okra accessions and select superior varieties with farmers’ preferred traits led to the evaluation of fifty (50) okra accessions on the field using a 5 x 10 α-lattice incomplete block design with three replications for three consecutive years (2019-2021). The analysis of variance showed high significant variation (p <0.001) for number of days to first flower, pod length and pod girth. Variability observed among the accessions will be useful for selection of potential parents needed for hybridization and generation of progenies with farmers’ desirable traits.